2010
DOI: 10.1155/2010/834926
|View full text |Cite
|
Sign up to set email alerts
|

Primary Biliary Cirrhosis: Environmental Risk Factors

Abstract: Abstract. Primary biliary cirrhosis (PBC) is an autoimmune disease of unclear etiology. It is a chronic, progressive condition that causes intrahepatic ductal destruction ultimately leading to symptoms of cholestasis, cirrhosis and liver failure. The disease predominantly affects middle aged Caucasian women. It has a predilection to certain regions and is found in higher incidences in North America and Northern Europe. It also has a genetic predisposition with a concordance rate of 60% among monozygotic twins.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Xenobiotics have also been implicated in the etiology of PBC. These commonly occur in pollutants, food preservatives, and pesticides 26. Atmospheric concentrations of pollutants are known to exhibit seasonal variation, providing support for a possible link with the onset of PBC 27, 28.…”
Section: Discussionmentioning
confidence: 95%
“…Xenobiotics have also been implicated in the etiology of PBC. These commonly occur in pollutants, food preservatives, and pesticides 26. Atmospheric concentrations of pollutants are known to exhibit seasonal variation, providing support for a possible link with the onset of PBC 27, 28.…”
Section: Discussionmentioning
confidence: 95%
“…These include infections such as Mycobacterium gordonae , Escherichia coli , and Novosphingobium aromaticivorans (2941). Other environmental factors that may display spatial variation include xenobiotics, which are present in pollutants (10). Lifestyle factors may also vary by social community and residential area.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggested that one or more spatially heterogeneous environmental agents may play a role in the etiology of PBC. Putative agents include infections, smoking, hair dyes, and xenobiotics (4, 710). …”
mentioning
confidence: 99%
“…A similar mechanism has been proposed for childhood precursor B-cell acute lymphoblastic leukaemia (Greaves, 1988). Possible infectious agents, indicated by other studies, include E. coli, Novosphingobium aromaticivorans, mycobacteria and human beta retrovirus (Butler et al, 1993(Butler et al, , 1995Haydon and Neuberger, 2000;Shimoda et al, 2000;Tsuneyama et al, 2001;Selmi et al, 2003;Xu et al, 2003;Kaplan, 2004;Olafsson et al, 2004; Possible non-infectious agents include xenobiotics that commonly occur in pollutants, food preservatives and pesticides (Dronamraju et al, 2010), as well as past or present smoking and previous pregnancies (Selmi et al, 2011). Whilst some of these factors suggest a long latency for the onset of clinical disease, the potential role of infectious agents -together with the seasonal pattern reported previously (McNally et al, 2011) -suggest that the latency may be short for certain risk factors.…”
Section: Type Of Analysis Time Period Within Months Within Quarters Wmentioning
confidence: 72%